2019
DOI: 10.1016/j.afos.2019.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of 6 osteoporosis risk assessment tools among postmenopausal women in Kuala Lumpur, Malaysia

Abstract: ObjectivesTo compare and assess the performance of 6 osteoporosis risk assessment tools for screening osteoporosis in Malaysian postmenopausal women.MethodsSix osteoporosis risk assessments tools (the Simple Calculated Osteoporosis Risk Estimation [SCORE], the Osteoporosis Risk Assessment Instrument, the Age Bulk One or Never Estrogen, the body weight, the Malaysian Osteoporosis Screening Tool, and the Osteoporosis Self-Assessment Tool for Asians) were used to screen postmenopausal women who had not been previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Recent research has shown that most of these tools were lacking precision (ranging from 0.04 to 0.12), and the simple calculated osteoporosis risk estimation (SCORE) had the best balance between recall and precision among the tested tools, and the AUC was the highest (0.072–0.161). [ 18 ] A study has tested FRAX without BMD, and they found its sensitivity to be 33.3% with a specificity of 86.4% and an AUC of 60% at a threshold of ≥9.3%,[ 19 ] while the AUC in our findings was around 90%. Ettinger et al .…”
Section: Discussionmentioning
confidence: 52%
“…Recent research has shown that most of these tools were lacking precision (ranging from 0.04 to 0.12), and the simple calculated osteoporosis risk estimation (SCORE) had the best balance between recall and precision among the tested tools, and the AUC was the highest (0.072–0.161). [ 18 ] A study has tested FRAX without BMD, and they found its sensitivity to be 33.3% with a specificity of 86.4% and an AUC of 60% at a threshold of ≥9.3%,[ 19 ] while the AUC in our findings was around 90%. Ettinger et al .…”
Section: Discussionmentioning
confidence: 52%
“…An interesting recent study demonstrated that during weight-loss programs, BMI can not specify the fat distribution, with limited use of this datum; in contrast with DXA report, which is able to quantify the metabolic re-distribution of total and regional fat mass and visceral adipose tissue [ 49 ]. Another study compared the accuracy of six different osteoporosis risk assessment tools in a restricted group of women in Kuala Lumpur, further demosntrating the importance of DXA in such context [ 50 ].…”
Section: Dxa: Beyond Bone Health Assessmentmentioning
confidence: 99%
“…The highest ethnic proportion in Singapore is the Chinese population (74.2%), while in Malaysia Bumiputera including the Malay population (approximately 70%) is the majority [ 26 , 27 ]. OSTA was found to be unsuitable to identify osteoporosis among postmenopausal women in a Malaysian study [ 28 ]. However, we need to be cautious in promoting FRAX alone as the screening modality for osteoporosis as it may or may not be cost-effective to screen with FRAX, depending on the setting [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%